1997
DOI: 10.1097/00006534-199705000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Are Breast Implants Anticarcinogenic? A 14-Year Follow-Up of the Los Angeles Study

Abstract: Endothelins are well-known vasoconstrictor peptides produced by vascular endothelial cells that have been reported to have a fundamental role in regulation of the systemic blood circulation. Plasma levels of endothelins are increased by burn injury, which also causes thrombosis and occlusion of vessels in the dermis as well as a vascular response in the adjacent uninjured dermis. Diminished blood flow leads to progressive ischemia and necrosis of the dermis beneath and around the burn (zone of stasis). If bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 17 publications
6
41
0
3
Order By: Relevance
“…Others have reported similar findings and concluded that women with cosmetic breast implants are not at increased risk of subsequent breast cancer (Berkel et al, 1992;Deapen et al, 1997;McLaughlin et al, 1998;Brinton et al, 2000b); on the contrary, a recent metaanalysis reported a 30% reduction of breast cancer risk among women with breast implants (RR ¼ 0.72; 95% CI 0.61 -0.85) and it was concluded that breast implants may confer a protective effect against breast cancer (Hoshaw et al, 2001). Several explanations for this protective effect have been put forward: activation of the immune response as result of foreign body reaction may enhance detection and degradation of precancerous lesions; compression of the glandular tissue from the implant may diminish blood perfusion, which may alter cellular metabolism, and a local decrease in body temperature caused by the implant could diminish cellular metabolism (Deapen et al, 1997;Brinton et al, 2000b;Hoshaw et al, 2001). However, different preoperative characteristics among women seeking breast implantation compared with other women could perhaps more likely account for the decreased breast cancer risk among implant women.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Others have reported similar findings and concluded that women with cosmetic breast implants are not at increased risk of subsequent breast cancer (Berkel et al, 1992;Deapen et al, 1997;McLaughlin et al, 1998;Brinton et al, 2000b); on the contrary, a recent metaanalysis reported a 30% reduction of breast cancer risk among women with breast implants (RR ¼ 0.72; 95% CI 0.61 -0.85) and it was concluded that breast implants may confer a protective effect against breast cancer (Hoshaw et al, 2001). Several explanations for this protective effect have been put forward: activation of the immune response as result of foreign body reaction may enhance detection and degradation of precancerous lesions; compression of the glandular tissue from the implant may diminish blood perfusion, which may alter cellular metabolism, and a local decrease in body temperature caused by the implant could diminish cellular metabolism (Deapen et al, 1997;Brinton et al, 2000b;Hoshaw et al, 2001). However, different preoperative characteristics among women seeking breast implantation compared with other women could perhaps more likely account for the decreased breast cancer risk among implant women.…”
Section: Discussionmentioning
confidence: 78%
“…There is no evidence that breast implants increase the risk of breast cancer (Brinton et al, 2000b;Mellemkjaer et al, 2000). On the contrary, several reports document that women with cosmetic breast implants seem to be at a lower risk of developing breast cancer (Berkel et al, 1992;Deapen et al, 1997;McLaughlin et al, 1998;Hoshaw et al, 2001). However, the issue of potential delay in breast cancer diagnosis in the augmented breast has been raised, since breast implants are radiopaque and this influences the sensitivity of mammography (Eklund et al, 1988;Hayes et al, 1988;Silverstein et al, 1992).…”
mentioning
confidence: 99%
“…Only 3 publications, including our previous report, showed a statistically significant shift toward more advanced breast tumors at diagnosis among augmented women (19)(20)(21). However, several other publications reported no statistically significant differences in breast cancer stage at diagnosis comparing augmented to nonaugmented women (6,9,12,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, specific implant characteristics such as implant volume and placement might affect the detection of breast cancer (36).…”
Section: Introductionmentioning
confidence: 73%
“…Although not statistically significant, several studies showed a tendency toward advanced breast tumors at diagnosis for women who received augmentation mammaplasty (6,(29)(30)(31)(32)(33)(34)(35). However, several other publications found little or no evidence that implant women were diagnosed at a later stage (9,12,(22)(23)(24)(25)(26)(27)(28)57). One possible explanation is the small number of breast cancer cases among augmented women cases), which may have affected study power in these studies.…”
Section: Principal Findings and Comparison With Previous Studiesmentioning
confidence: 90%
“…None of these observations have been substantiated in epidemiologic studies, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and in 2000 an independent review board concluded that the available evidence does not support an association between silicone breast implants and breast carcinoma or sarcoma, multiple myeloma or lymphoma. 25 In 2001, Brinton et al reported increased incidence of and mortality from respiratory and brain cancer among 13,488 women with cosmetic breast implants compared to women in the general population and 3,936 plastic surgery controls.…”
Section: -10mentioning
confidence: 99%